Oñati Proceedings: Contributions to psycho-sociology of law - García Ramos, José Ignacio (dir.) (1991)
Contiene: A contribution to the psycho-sociology of psychopathy; Bibliographical Review of Antisocial Personality Disorder and Society: 1980-1990; Abuses in psychiatry: Law reform in Japan july1990; Attitudes toward authority in juvenile delinquents; A contribution to the containment of pasychopathy.